EFEKTIVITAS PENGELOLAAN ALOKASI DANA DESA DALAM PEMBANGUNAN FISIK DI DESA BATUJAJAR TIMUR KABUPATEN BANDUNG BARAT - Dzenta Mashita; Yamardi Yamardi; Toto Kushartono (Jurnal Caraka Prabu, 2019)
The problems that occur in Batujajar Timur Village are the mismatch of village fund allocations received according to the realization, the delay in disbursing village fund allocations, the uneven physical development in Batujajar Timur Village. The management of village fund allocations cannot be said to be effective, if it is reviewed correctly, quickly, economically, and safely. This study uses a descriptive research method with a qualitative approach. The data obtained through the results of library research, field studies through in-depth interviews and observations, and documentation. The results showed that the management of Village Fund Allocation in Physical Development in Batujajar Timur Village, Batujajar Subdistrict, West Bandung Regency, cannot be said to be effective, due to the lack of community participation in musrenbangdes, the village fund allocation received is not by government regulations which in theory were obtained in January. and it was reported in December, the facilities for infrastructure funds were not yet supported, the allocation of village funds obtained did not match the realization. Keywords: Effectiveness, Management, Village Fund Allocation, Development